Examination of the Impact of Work System Variables on Job Satisfaction Utilizing the MOQS Methodology - Ma'ruf, Farid; Zuhair, Muhammad Hanif (Universitas Kristen Maranatha, 2024)
UKM BRIQCO is an SME in Yogyakarta that produces coconut shell charcoal. The results of interviews with the owner obtained an attendance rate that is not by the standard, which is at least 90%, with an indication of worker dissatisfaction with the work system implemented. This study aims to determine the effect of the work system on job satisfaction using the MOQS method. Macroergonomic Organizational Questionnaire Survey (MOQS) is a macro ergonomic method to identify symptoms of design problems in work system factors. In addition, this study uses SPSS to process the data statistically. There are 32 respondents, and six variables were used in this study. These variables consist of 5 independent variables and one dependent variable. Based on data processing, it was obtained that independent variables simultaneously affect job satisfaction. The partial test showed that individual characteristics are a work system factor that affects job satisfaction. At the same time, other variables do not affect job satisfaction. After the analysis and discussion, suggestions that can be recommended include evaluating the workload to be evenly distributed, providing rewards and punishments, and providing work motivation to increase enthusiasm and loyalty to the company.